E-Trust, Perceived Ease Of Use, E-Satisfaction And E-Loyalty For Users Of The Tiktok Shop Application - Rahmawati, Amanda; Ramli, Abdul Haeba (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Determinant of Online Shop Customers Loyalty ______279 Submitted: NOVEMBER 2023 Accepted: JANUARI 2024 This study aims to prove that the relationship between the influence of E-Trust, Perceived Ease Of Use and E-Satisfaction on E-Loyalty is shown to consumers in Tiktok Shop e-commerce. The variables used in this study are E-Trust, Perceived Ease Of Use, E-Satisfaction, and E-Loyalty. The sample selection criteria for this study are Tiktok Shop customers who make purchases through the Tiktok Shop marketplace, use Tiktok Shop regularly for the last 6 months, live in Jakarta, Bogor, Depok, Tangerang, and Bekasi (JABODETABEK) and are 17 years and over. This study uses data analysis techniques, namely Structural Equation Modeling (SEM), with SmartPLS software. Based on the research results, of the 5 hypotheses, 4 hypotheses are accepted, namely E-Trust has a positive effect on E-Satisfaction, Perceived ease of use has a positive effect on E-Satisfaction, E-Satisfaction has a positive effect on E-Loyalty, and Perceived Ease Of Use has a positive effect on E-Loyalty. The contribution of this research is to understand the factors that influence E-satisfaction in the context of Tiktok Shop which can help marketplace companies to create more effective marketing strategies in increasing user satisfaction in the Tiktok Shop application.. Keywords: e-trust, perceived ease of use, e-satisfaction, e-loyalty.